Taymāʾ II Catalogue of the Inscriptions Discovered in the Saudi-German Excavations at Taymāʾ 2004-2015 - Macdonald, Michael C.A (Archaeopress Publishing, 2021)
Taymāʾ II is a Catalogue which contains all the inscriptions discovered during the 24 seasons of the Saudi- German excavations at Taymāʾ from 2004-15 which were funded by the German Research Foundation (DFG). The 113 objects carry inscriptions in different languages and scripts, illustrating the linguistic diversity of the oasis through time. Although the majority are fragmentary, they provide an important source for the history of the oasis in ancient and mediaeval times.The Babylonian cuneiform inscriptions in this volume confirm for the first time the ten-year sojourn at Taymāʾ of the last Babylonian king Nabû-na'id (556-539 BC). In addition, Imperial Aramaic inscriptions dated by the reigns of Lihyanite kings, based at Dadan (modern al-ʿUlā), reveal for the first time that they ruled Taymāʾ at a period in the second half of the first millennium BC.As well as editing the volume, Michael C. A. Macdonald edited the Imperial Aramaic inscriptions found from 2010-15, plus those in the form of the Aramaic script which developed in Taymāʾ, and the Nabataean, Dadanitic, and Taymanitic texts. In addition, Hanspeter Schaudig edited the cuneiform inscriptions; Peter Stein, the Imperial Aramaic texts found from 2004-09; and Frédéric Imbert, the Arabic inscriptions. Arnulf Hausleiter and Francelin Tourtet provided archaeological contributions, while Martina Trognitz curated the virtual edition of many of the texts recorded by RTI. The indexes contain the words and names from all known texts from the oasis, including those in the Taymāʾ Museum and other collections which will be published as Taymāʾ III.